INTERNALISASI NILAI KEBERKAHAN MELALUI KEGIATAN EDUPRENEURSHIP ISLAMI DI MI SALAFIYAH DADIREJO - Atiyah, Atiyah; Salim, Muhlisin; Bambang, Bambang (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to analyze the process of internalizing the value of blessing through Islamic edupreneurship activities and its impact on the character of students at MI Salafiyah Dadirejo. Methods: This study used a qualitative approach with a case study. Data collection techniques included participant observation, in-depth interviews with the principal, teachers, students, and parents, and documentation studies. Data analysis used the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that the internalization of the value of blessing in Islamic edupreneurship activities at MI Salafiyah Dadirejo occurs through three main stages: (1) the Value Transformation Stage, where the values ??of honesty (amanah), work ethic (jihad), and social concern (sadaqah) begin in business planning; (2) the Value Transaction Stage, which occurs during a market simulation (Market Day) where students not only engage in buying and selling transactions but also practice greetings, gratitude, and sharing profits; and (3) the Transinternalization Stage, where post-activity reflection and habituation instill the understanding that blessed sustenance is not only about quantity, but also about its usefulness and God's pleasure. As a result, students not only become more independent and self-confident, but also demonstrate a higher level of gratitude, honesty, and caring. This study provides a concrete perspective on how Islamic spiritual values, particularly